Construction of seismic portraits of important events provided that their observation is not available - Бріцький , О. І. (Інститут проблем реєстрації інформації НАН України, 2021)
An approach to obtaining seismic portraits of important events is presented, provided that their observation is not available. The movement of heavy equipment and the shots of certain types of artillery weapons such as mortars and howitzers were classified as important events. In the future, the proposed approach can be extended to aircraft. The essence of the proposed approach is that seismic portraits of the events of interest from the accessible side are determined first. Then, the principle of a moving window is used which has a time size corresponding to the assumed seismic portrait. The window is discretely shifted along the time axis on the seismogram from the inaccessible side. In each position of the window, the cross-correlation function of the process is calculated in the window with a known portrait from the accessible side. When the maximum is obtained, the time to reach it is recorded. The seismic portrait of interest is for this time on the seismogram from the inaccessible side on an enlarged scale. It is shown that seismic portraits of heavy equipment movement and mortar shots are in the range of hertz units, and howitzers are fired in the range of tens of hertz. They also vary considerably in duration. The obtained seismic portraits can be used to solve the problems of location and identification of important seismic events.. Fig.: 12. Refs: 10 titles.